Integrative description of Thaeides ramoni sp. nov. (Lepidoptera: Lycaenidae), a sympatric sibling species of Thaeides theia (Hewitson, 1870) found in the Sierra Nevada de Santa Marta, Colombia - Prieto, Carlos; Pinilla, Claudia; Lorenc-Brudecka, Jadwiga; Balke, Michael (Zootaxa, 2024)
We present evidence from DNA barcodes, wing pattern and distribution to support the hypothesis that an entity flying in sympatry with Thaeides theia in the Sierra Nevada de Santa Marta, is an undescribed biological species named herein as Thaides ramoni Prieto, sp. nov. Adult specimens and genital structures are illustrated for both species along with molecular and morphological diagnostic characters. In addition, we present some considerations about the taxonomy of the species in the Thaeides muela group.